Faktor-faktor yang Mempengaruhi Pemanfaatan Pelayanan Kesehatan di Poli Lansia Puskesmas Pejagoan Kabupaten Kebumen Tahun 2022 - Fajarwati, Dian; Intiasari, Arih Diyaning; Kurniawan, Arif (Jurnal Kesehatan Masyarakat, 2023)
The increase in the elderly population needs attention. This is because the morbidity rate in the elderly is higher compared to other age groups. Health service coverage for the elderly is still low. The use of preventive and curative health services at the Pejagoan Health Center Elderly Polyclinic in 2022 is still not optimal and is experiencing a decline. This study aims to identify the factors that influence the utilization of health services in the elderly in the working area of the Pejagoan Health Center. This research is a quantitative analytic study with a cross-sectional research design. The research sample is 104 people. Sampling was carried out using proportional random sampling. The instrument used is a questionnaire. Data analysis was performed using univariate analysis, bivariate analysis through chi square test, and multivariate analysis through multiple logistic regression tests.The results showed that 45.2% of the elderly had used health services at the Elderly Poly. Factors related to the utilization of health services in the Elderly Poly are education, employment, income, health insurance, accessibility, family support, and perceptions of illness. The factor that has the most influence on the utilization of health services at the Pejagoan Health Center Elderly Poly is the ownership of health insurance.Ownership of health insurance is the factor that most influences the utilization of services at the Pejagoan Health Center Elderly Poly.